2023
DOI: 10.1002/bio.4532
|View full text |Cite
|
Sign up to set email alerts
|

Mechanofluorochromic behaviours of functionalized carbazole‐based difluoroboron compounds with different aryl substituents moieties

Abstract: To better understand the relationship between molecular structure and mechanofluorochromic characteristics, three carbazole‐based N^O‐chelated difluoroboron compounds (Cz‐S‐BF2, Cz‐PhNp‐S‐BF2, and Cz‐BNp‐S‐BF2) with different aryl substituents moieties were designed and synthesized. The mechanofluorochromic behaviours of Cz‐S‐BF2 (luminescence from bluish‐green to yellowish‐green, emission from 504 to 535 nm) without aryl substitution and Cz‐PhNp‐S‐BF2 (luminescence from green and yellow, emission from 521 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Nevertheless, either the luminescence color or the emission wavelength of ts‐2NA BF 2 had little change under external mechanical stimulation. This was consistent with our previous reports that a better coplanarity originated from the binaphthyl substituent group [36]. Meanwhile, we found that the emitting colors and emission peaks of ts‐Ph BF 2 and ts‐TPA BF 2 could be recovered to their original states by CH 2 Cl 2 vapor fuming for 30 s, which indicates that ts‐Ph BF 2 and ts‐TPA BF 2 had reversibly MFC behaviors.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, either the luminescence color or the emission wavelength of ts‐2NA BF 2 had little change under external mechanical stimulation. This was consistent with our previous reports that a better coplanarity originated from the binaphthyl substituent group [36]. Meanwhile, we found that the emitting colors and emission peaks of ts‐Ph BF 2 and ts‐TPA BF 2 could be recovered to their original states by CH 2 Cl 2 vapor fuming for 30 s, which indicates that ts‐Ph BF 2 and ts‐TPA BF 2 had reversibly MFC behaviors.…”
Section: Resultssupporting
confidence: 92%
“…Because ts‐TPA BF 2 displayed the most distinct redshift (21 nm) under external mechanical stimulation and remarkable reversible chromatism by grinding–fuming process compared with the other three complexes, ts‐TPA BF 2 ‐based ink‐free rewritable paper for information encryption and decryption was explored. According to previous reports [36, 49], a Whatman filter was immersed into 10 mL of CH 2 Cl 2 in which 10 mg of ts‐TPA BF 2 solid powder was dissolved for 10 min, and then the immersed filter paper was dried by airing on an A4 paper as safety paper. The prepared safety paper emitted yellow luminescence under 365 nm irradiation, as shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we found that the introduced different aryl substituents moieties in 3‐position of carbazole skeleton had a significantly influence on the MFC behaviors of the carbazole‐based salicylaldimine difluoroboron compounds due to different steric hindrance effects, [22] and the indole‐based difluoroboron compounds with triphenylamine group not only exhibited remarkable MFC behavior, but also could be achieved rewritable storage [23] . Therefore, we envisaged that indole unit was modified using aromatic groups to achieve excellent MFC performance.…”
Section: Introductionmentioning
confidence: 99%